Interpretasi Makna Peranti dalam Tradisi Besentulak di Dusun Sedau Barat, Lombok Tengah: Kajian Semiotika Roland Barthes: Interpretation of the Meaning of Devices in the Besentulak Tradition in West Sedau Village, Central Lombok: A Semiotic Study by Roland Barthes - Hirwan Jayadi; Saharudin Saharudin; M. Syahrul Qodri; Aswandikari Aswandikari (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2026)
This study examines diverse public perceptions of the Besentulak tradition in West Sedau Hamlet, stemming from a lack of philosophical understanding of the ritual instruments used. This absence of a complete meaning has implications for the emergence of diverse, even contradictory, interpretations within the community. Using Roland Barthes's semiotic approach, which includes analysis at the levels of denotation, connotation, and myth, this qualitative study aims to dissect the meanings of eleven ritual instruments positioned as the main lexia within the tradition's structure. Data collection was conducted through participant observation and in-depth interviews with traditional leaders and kiai, who serve as representatives of cultural and religious authority. The results of the study indicate that the ritual instruments in Besentulak function not merely as material objects, but as a system of signification capable of transforming physical objects into symbolic texts loaded with the ideology of salvation. At the connotative level, these instruments represent the values of monotheism, cosmic harmony, and total submission to Allah SWT. The conclusion of this study confirms that the besentulak devices serve as a cultural defense mechanism and an acculturation strategy for the Sasak people as they navigate social dynamics. The scientific contribution of this research lies in mapping meaning at the micro level, thereby strengthening the spiritual integrity of the tradition. However, this research is limited by its single geographic scope, so cross-regional comparative studies are needed to enrich future findings.